Multirate-sampling adaptive controller for an induction generator driven by a wind turbine - Sotelo-Neyra, Víctor Manuel; Paredes-Larroca, Fabricio Humberto (2018)
This paper deals with the development of a technology for a wind driven induction generator system. Its goal is the modeling, design and analysis of an electronic controller using a multi-rate sampling adaptive algorithm, with a structure made of several control strategies, each one with different sample times and having a different weight or influence in the final solution in the control problem. In low power wind turbines, the best power conditions for harvesting the energy is to search for an optimal rate of the tip blade speed and the wind speed called lamda ¿, giving an optimal torque as a set point. The adaptability comes from the weights that are giving importance or higher priority to the control strategy transfer function. In the presence of sudden changes and winds changing rapidly, high frequency strategies take more importance and greater values, with calm winds the low frequencies take command with greater weights. The frequencies can bet set to avoid damage to the mechanical systems as the turbine blades. A field-oriented torque controller in cascade is used, regulating the magnetic field and the torque.